Preparation method and application of high-refractive-index contrast patternable long-afterglow photonic crystal

CN122941405APending Publication Date: 2026-10-20NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610961947.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-20

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a method for preparing and applying a patternable long-persistence photonic crystal with high refractive index contrast, addressing the current technical problems of limited optical information in materials and low refractive index contrast between photonic crystal microspheres and the medium, resulting in dark structural colors and difficulty in patterning and storing information. This invention designs and synthesizes a composite microsphere with a "core@composite shell@shell" structure. After the microspheres self-assemble into a photonic crystal, patterning is achieved through selective laser etching. The method employs a wet chemical method to prepare monodisperse ZnS nanoparticles. A SiO2 shell is grown on the surface of the ZnS particles using a modified Stöber method. A hydrothermal reaction is then used to encapsulate luminescent molecules within the SiO2 shell. Subsequently, an undoped SiO2 layer is coated on the outermost layer, ultimately yielding a core-shell structured ZnS@luminescent molecule-doped SiO2@SiO2 composite microsphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical materials technology, specifically relating to a method for preparing and applying a patternable long afterglow photonic crystal with high refractive index contrast. Background Technology

[0002] Photonic crystals are artificial microstructure materials with periodically arranged dielectric constants (or refractive indices). Their core characteristic is the ability to form photonic band gaps, thereby effectively controlling photon propagation behavior. Combining long-persistent luminescent materials with photonic crystals allows the structure to continue emitting light even after excitation ceases. Furthermore, by adjusting the matching degree between the emission peak position of the long-persistent material and the photonic band gap, the intensity of the afterglow emission can be effectively controlled. Integrating long-persistent luminescence and the photonic band gap effect into a single optical platform fuses multiple optical information, significantly increasing the complexity and capacity of optical encoding, thus demonstrating unique application potential in information storage and high-end anti-counterfeiting fields.

[0003] However, current methods for preparing long-afterglow photonic crystals still have the following limitations in achieving their high-performance applications:

[0004] 1. Insufficient optical control capability: The low refractive index contrast between the microspheres constituting the photonic crystal and the medium results in a weak intensity of the formed photonic bandgap reflection peak. This fundamentally weakens the structure's ability to control long-afterglow luminescence, making it difficult to fully leverage the advantages of "multi-dimensional control".

[0005] 2. Limitations in micro / nano fabrication precision: Existing processes struggle to achieve high-precision, high-resolution complex patterning on photonic crystal thin films. This restricts the practical application of this material in integrated micro / nano optical devices and sophisticated optical anti-counterfeiting labels.

[0006] 3. Challenges exist in the compatibility of function and structure: the way the long-afterglow luminescent center is combined with the photonic crystal structure may affect its luminescence performance or structural stability.

[0007] Therefore, there is an urgent need and great significance to develop a photonic crystal preparation method that can achieve high refractive index contrast, fine patterning capability, and excellent long afterglow performance. Summary of the Invention

[0008] The purpose of this invention is to solve the technical problems of limited optical information in current materials, low refractive index contrast between photonic crystal microspheres and the medium, dark structural color, and difficulty in patterning and storing information. The invention provides a method for preparing and applying a patternable long afterglow photonic crystal with high refractive index contrast.

[0009] The concept of this invention:

[0010] To fully explore the application value of long-persistent photonic crystals in information storage and anti-counterfeiting, this invention systematically analyzes the bottlenecks in the application of existing long-persistent photonic crystal materials in anti-counterfeiting and information storage, and finds the following prominent problems in the existing technology: 1) Traditional photonic crystals are mostly constructed using polymer or silica microspheres, which have low refractive index contrast, resulting in dull structural colors and limiting practical applications; 2) When introducing light-emitting function, the overall doping method is usually adopted, which makes the light-emitting molecules prone to aggregation or leakage, and affects the orderly assembly of photonic crystals; 3) Patterning processing mostly uses template method or photoresist-assisted etching, which is complex and has limited precision, making it difficult to achieve rapid preparation of micron-level fine patterns.

[0011] To address the aforementioned issues, this invention aims to develop a novel fabrication method that simultaneously meets three core requirements: high refractive index contrast for effective optical control, high-precision patterning capability to meet device integration needs, and excellent and stable long-afterglow luminescence performance, thereby achieving true multi-dimensional and highly complex optical information coupling.

[0012] To this end, this invention aims to enhance refractive index contrast using high-refractive-index ZnS as the core, and to confine long-afterglow luminescent molecules within the SiO2 interlayer using a "stepwise encapsulation" strategy. This maintains luminescence stability while avoiding interference with the self-assembly of the photonic crystal. Precise patterning is then achieved through laser direct writing technology, ultimately yielding a dual-mode responsive photonic crystal with bright structural color and patternable afterglow emission. The entire process involves four key steps: material synthesis, core-shell structure construction, self-assembly, and laser etching. The mechanisms of each step are as follows: monodisperse ZnS nanoparticles are prepared using a wet chemical method; the improved Stöber method and hydrothermal encapsulation complete the stepwise construction of the core-shell structure; the Czochralski method achieves the self-assembly of the three-dimensional photonic crystal; and a mid-infrared carbon dioxide laser direct writing system is used for etching and patterning the photonic crystal.

[0013] To achieve the above objectives, the technical solution provided by this invention is:

[0014] A method for preparing a high refractive index contrast patternable long afterglow photonic crystal, characterized by the following steps:

[0015] 1) Preparation of ZnS@SiO2 particles

[0016] 1.1) Monodisperse ZnS nanoparticles with uniform morphology and a particle size of 100-170 nm were prepared by wet chemical method; controlling the particle size within this range can provide a high refractive index contrast with the surrounding medium, which is conducive to the appearance of structural color;

[0017] 1.2) The ZnS nanoparticles obtained in step 1.1) are uniformly coated with a SiO2 shell with a thickness of 15-80 nm using the improved Stöber method to obtain ZnS@SiO2 particles. The SiO2 shell mainly serves as an active surface for subsequent encapsulation reactions. Its O-Si-O network structure can form a strong spatial confinement and rigid fixation effect on guest molecules, stabilizing triplet excitons.

[0018] 2) Preparation of ZnS@luminescent molecular doped SiO2 particles

[0019] The luminescent molecule solution with long afterglow luminescence potential and the ZnS@SiO2 particle dispersion obtained in step 1) were uniformly dispersed in deionized water and placed in a high-pressure reactor for hydrothermal reaction. The luminescent molecules were encapsulated in the SiO2 shell of the ZnS@SiO2 particles to obtain ZnS@luminescent molecule-doped SiO2 particles. At this time, the luminescent molecule-doped SiO2 shell on the outer layer of the ZnS nanoparticles is a luminescent composite shell. Under hydrothermal conditions, the luminescent molecules can be encapsulated in the SiO2 matrix through a dissolution-redeposition mechanism. Its network structure fixes the triplet excitons, forming the aforementioned "luminescent composite shell". This step achieves a tight combination of the luminescent unit and the microsphere structure.

[0020] 3) Preparation of ZnS@luminescent molecular doped SiO2@SiO2 composite microspheres

[0021] The ZnS@luminescent molecule-doped SiO2 particles obtained in step 2) are uniformly coated with a 5-10 nm thick SiO2 shell using a modified Stöber method to obtain ZnS@luminescent molecule-doped SiO2@SiO2 composite microspheres. These microspheres have a core-shell structure, and the outermost SiO2 shell plays multiple roles: ① It further protects the internal luminescent molecules, immobilizes triplet excitons, and weakens their non-radiative transitions. ② It improves the chemical properties of the microsphere surface, increasing the proportion of silanol groups and raising the surface potential, which is beneficial for subsequent self-assembly to form high-quality photonic crystals. Specifically, the SiO2 microsphere surface has a large number of Si-O atoms. -The ZnS@SiO2 particles, carrying a negative charge, experience a significant reduction in surface negative charge after hydrothermal reaction. Since the self-assembly of photonic crystals relies on electrostatic repulsion between particles, the assembly quality decreases after the hydrothermal reaction. Therefore, re-coating the outermost layer with a SiO2 shell improves its surface chemical properties, which is beneficial for the self-assembly and arrangement of the photonic crystal. Simultaneously, the outermost SiO2 shell should not be too thick, as this would reduce the refractive index of the composite microspheres. ③ By fixing the final size and morphology of the microspheres, a stable and well-dispersed ZnS@luminescent molecule-doped SiO2@SiO2 composite microsphere is obtained. The refractive index range of this composite microsphere is 1.49-1.69, which ensures a high refractive index contrast. This high refractive index contrast allows the reflection peak intensity of the three-dimensional photonic crystal prepared from the composite microspheres to be 2.2 times that of a photonic crystal composed of pure SiO2 microspheres.

[0022] 4) Preparation of three-dimensional long afterglow photonic crystals

[0023] The ZnS@luminescent molecule-doped SiO2@SiO2 microspheres obtained in step 3) were fabricated into a three-dimensional long-persistence photonic crystal using a vertical dip-coating method. This material combines structural color and long persistence, enabling the control of long-persistence luminescence through photonic bandgap, thus integrating multiple pieces of information onto a single optical platform.

[0024] Furthermore, step 1) specifically involves:

[0025] 1.1) Polyvinylpyrrolidone was dissolved in deionized water and sonicated to obtain a homogeneous and transparent solution. The solution was heated to 70-80℃ and kept stable before adding thioacetamide. After 10-15 minutes, concentrated nitric acid was added, and stirring was continued for approximately 10-15 minutes to completely hydrolyze the thioacetamide, resulting in a clear and transparent reaction system solution. Simultaneously, zinc nitrate hexahydrate was dissolved in deionized water and rapidly added to the reaction system with a stirring speed of 1000 r / min to form smaller particles. After 3 minutes, the stirring speed was reduced to 500 r / min, and the reaction was continued for 2-5 hours. After the reaction was completed, the mixture was washed with deionized water to obtain monodisperse ZnS nanoparticles with uniform morphology and a particle size of 100-170 nm. These ZnS nanoparticles serve as a high refractive index core (n=1.91), providing the basis for the high refractive index contrast of the final photonic crystal. Thioacetamide was used as the sulfur source, zinc nitrate hexahydrate as the zinc source, and polyvinylpyrrolidone as the surfactant. In the reaction system, the total reaction liquid volume was 80... The concentration of polyvinylpyrrolidone (PVP) is 0.27-0.63 mol / L (based on the repeating unit C6H9NO of PPVP, with a molecular weight of 111), the concentration of the sulfur source is 0.20-0.33 mol / L, and the concentration of the zinc source is 0.067-0.168 mol / L (based on Zn) 2+(Calculated); and the molar concentration ratio of the polyvinylpyrrolidone, sulfur source and zinc source is (3.0-4.2):(1.6-2.4):1; preferably, the concentration of the polyvinylpyrrolidone is 0.45 mol / L, the concentration of the sulfur source is 0.25 mol / L, the concentration of the zinc source is 0.125 mol / L, and the molar concentration ratio of the three is 3.6:2:1;

[0026] 1.2) The ZnS nanoparticles obtained in step 1.1) were washed and dispersed in ethanol, then mixed with deionized water and ammonia in a volume ratio of 4:1:1 at room temperature for 20 min to achieve uniform mixing. Subsequently, tetraethyl silicate and an equal volume of ammonia solution were added at a rate of 3.8 μL / min. -1 The ZnS@SiO2 particles were obtained by dripping the solution at a certain rate and stirring for 6 hours. At this dripping rate, the reaction was more complete and the product was more uniform.

[0027] In this process, 10 mL of ZnS nanoparticles were added to every 20 mL of ethanol, and then mixed thoroughly with deionized water and ammonia at a volume ratio of 4:1:1 at room temperature. The mixture was then dispensed at a rate of 3.8 μL / min. -1 Add 0.35-1.3 mL of tetraethyl silicate and an equal volume of ammonia solution dropwise (controlled by a microfluidic device).

[0028] Further, in step 2), the luminescent molecule with long afterglow luminescence potential is a nitrogen-doped carbon dot, 4-phenylpyridine or 4,4'-bipyridine, which is obtained by hydrothermal reaction to ZnS@luminescent molecule-doped SiO2 particles;

[0029] The hydrothermal reaction temperature is 80-200℃, and the reaction time is 0.5-4 h, preferably 140℃ for 3 h;

[0030] If the luminescent molecule with long afterglow luminescence potential is nitrogen-doped carbon dots, then the mass ratio of nitrogen-doped carbon dots to ZnS@SiO2 particles is 1:25. The resulting product, ZnS@carbon dot-doped SiO2 particles, is obtained through a hydrothermal reaction. Specifically, the nitrogen-doped carbon dot solution is prepared using ethanolamine as both a carbon and nitrogen source, and phosphoric acid as a catalyst to provide the necessary acidic environment for the reaction, via a microwave-assisted method. Ethanolamine and phosphoric acid are mixed at a specific molar ratio and reacted in a microwave reactor at a specific temperature for a certain period. After the reaction is complete, the resulting solution is purified through dialysis and filtration to obtain a nitrogen-doped carbon dot solution with good water dispersibility and luminescence properties.

[0031] Furthermore, step 3) specifically involves:

[0032] First, the ZnS@luminescent molecularly doped SiO2 particles obtained in step 2) are dispersed in ethanol, then mixed with deionized water and ammonia at a volume ratio of 4:1:1 at room temperature. Subsequently, tetraethyl silicate and an equal volume of ammonia solution are added at a rate of 3.8 μL / min. -1 The solution was added dropwise at a certain rate, and the mixture was stirred for 2 h to obtain ZnS@luminescent molecule-doped SiO2@SiO2 composite microspheres.

[0033] In this process, 50 mg of ZnS@luminescent molecularly doped SiO2 particles were added to every 10 mL of anhydrous ethanol. These particles were then mixed thoroughly with deionized water and ammonia at a volume ratio of 4:1:1 at room temperature, and the mixture was further diluted at a rate of 3.8 μL / min. -1 0.15 mL of tetraethyl silicate and an equal volume of ammonia solution were added dropwise. Since the outermost SiO2 shell primarily improves the chemical properties of the particle surface to ensure the quality of the subsequent Czochralski (CZ) dip-coating process for photonic crystals, its thickness is mainly determined by the SiO2 intermediate shell layer initially coated on the ZnS particle surface. To ensure a consistent outermost layer thickness, a fixed amount of tetraethyl silicate was added dropwise in this invention.

[0034] Further, step 4) specifically involves:

[0035] The ZnS@luminescent molecularly doped SiO2@SiO2 composite microspheres obtained in step 3) were dispersed in anhydrous ethanol with a mass fraction of 6-10 wt% to form a dispersion. A clean substrate was vertically immersed in the dispersion using a vertical dip-pick method at a depth of 2 μm. -1 The three-dimensional long-afterglow photonic crystal was obtained by dip-coating the substrate 4-8 times at a speed of 2 μm s. -1 The optimal pulling speed is found, representing a balance between capillary force, convection assembly, and gravity. Under the influence of capillary force and solvent evaporation, the microspheres self-assemble and arrange themselves into a three-dimensional ordered close-packed structure on the substrate surface, forming a three-dimensional photonic crystal thin film. The high-refractive-index composite microspheres give this photonic crystal a more significant photonic bandgap.

[0036] Furthermore, in step 4), the substrate is a glass substrate. Glass substrates possess excellent optical transparency, extremely high surface flatness, hydrophilicity, and good chemical stability, resulting in photonic crystals of the highest quality prepared by Czochralski impregnation on glass substrates.

[0037] The present invention also provides a high refractive index contrast patternable long afterglow photonic crystal prepared by the above method, and the application of the long afterglow photonic crystal in the preparation of optical anti-counterfeiting marks or dynamic information storage media.

[0038] Based on the above applications, this invention also provides an optical anti-counterfeiting label or dynamic information storage medium and its preparation method. Specifically, according to requirements, a preset pattern is processed on the aforementioned high refractive index contrast patternable long-persistence photonic crystal using laser etching technology. Laser etching selectively removes composite microspheres from certain areas, forming a long-persistence photonic crystal thin film with a specific pattern. The preset pattern is used for micro-coding of information storage or micro-labeling for anti-counterfeiting. The long-persistence photonic crystal with a specific pattern includes a substrate and a three-dimensional ordered structure located thereon. This three-dimensional ordered structure is periodically arranged from the aforementioned composite microspheres (also called constructed microspheres) and has a preset pattern formed by laser etching. It has the following optical properties: after ultraviolet light excitation stops, the preset pattern area can exhibit long-persistence luminescence; under natural light, the preset pattern area exhibits a bright structural color, and this structural color undergoes a blue shift as the viewing angle increases.

[0039] When selectively scanning and etching a three-dimensional long-persistence photonic crystal using a laser beam, the power, scanning path, speed, and scanning accuracy of the laser can be precisely controlled to selectively remove microspheres from specific areas of the photonic crystal film. This allows for the fabrication of pre-defined patterns (such as text, graphics, QR codes, microstructures, etc.) on a background of an intact photonic crystal film. In the laser-etched areas, the photonic crystal structure is destroyed, and the long-persistence luminescence capability disappears, while the unetched areas retain their original photonic crystal structure and long-persistence luminescence performance. Therefore, the resulting patterned areas exhibit angle-dependent bright structural colors under ordinary illumination. Furthermore, after external excitation (such as ultraviolet light) ceases, a clear long-persistence luminescence pattern defined by the laser etching path further emerges on the film, thus achieving the integration of static structural colors and dynamic afterglow luminescence—both optical information. Mid-infrared lasers can be used, and precise pattern construction can be achieved by adjusting laser parameters (such as power, scanning speed, and scanning accuracy).

[0040] The principle of this invention:

[0041] This invention achieves synergistic optimization of high refractive index contrast, excellent long afterglow performance, and fine patterning capability. Its principle can be summarized in the following three aspects:

[0042] 1. The principle of high refractive index contrast and its contribution to structural color brightness: The structural color of photonic crystals originates from the Bragg diffraction of light of a specific wavelength by a periodic dielectric structure. The position of its reflection peak is determined by Bragg's law, while the reflection intensity (i.e., structural color brightness) depends on the refractive index contrast of the material and the degree of order in the arrangement of microspheres. The refractive index contrast is defined as... ,in The refractive index of high refractive index materials, The refractive index is the refractive index of a low-refractive-index material (typically air or a medium). This invention uses ZnS as the core material, with a refractive index of approximately 1.91, significantly higher than that of traditional polymers (approximately 1.5) or SiO2 (approximately 1.45). Based on the formula for calculating the refractive index of core-shell composite microspheres, the refractive index range of the composite microspheres is 1.49-1.69. The high refractive index contrast between the composite microspheres and the surrounding medium (air) significantly enhances the interaction between light and the periodic structure. According to photonic crystal theory, high refractive index contrast can broaden the photonic bandgap and enhance the photonic state density at the bandgap edge, thereby greatly increasing the intensity of the reflection peak and resulting in a bright and saturated visual effect for the structural color.

[0043] The refractive index of core-shell composite microspheres is calculated using the equivalent medium approximation method (EMA). Its "effective refractive index" can be calculated by weighting the refractive indices of the core and shell materials by volume fraction. The most commonly used simplified model is linear volume fraction weighting, also known as the "mixing rule".

[0044] 2. Principle of Excellent Long Afterglow Performance: The achievement of long afterglow performance relies on the effective introduction and stable maintenance of luminescent molecules. Encapsulation Protection Mechanism: A double-shell structure of "inner SiO2 encapsulation + outer pure SiO2 isolation" is adopted. The luminescent molecules are encapsulated within the inner SiO2 shell, which provides strong spatial confinement and rigid fixation for guest molecules, stabilizing the triplet exciton. Simultaneously, the outermost SiO2 matrix possesses chemical inertness, thermal stability, and photostability, effectively isolating the luminescent molecules from environmental factors such as oxygen and moisture, extending the afterglow lifetime. Furthermore, the SiO2 shell is transparent to ultraviolet light, not affecting excitation efficiency. Synergistic Effect of Patterned Afterglow: After laser etching, the microspheres in the patterned area are removed and no longer possess luminescence capability; the microspheres in the unetched area retain their complete core-shell structure, maintaining the long afterglow performance. Therefore, after ultraviolet excitation stops, the observed afterglow pattern complements the laser-etched portion, achieving dual-modal information storage and significantly enhancing its application potential in high-end anti-counterfeiting fields.

[0045] 3. Principle of High-Quality Assembled Three-Dimensional Photonic Crystals: The preparation of high-quality colloidal photonic crystals using the Czochralski method requires sufficiently strong electrostatic repulsion on the surface of the microspheres to overcome van der Waals forces, thereby maintaining the colloidal stability and ordered arrangement of the system. The initial ZnS@SiO2 particles have a large number of silanol groups (Si-OH) on their SiO2 shell surface, which deprotonate in aqueous solution (Si-O...). -The process involves forming a high-density negative charge layer and a thick diffused double layer. Strong repulsive forces force the microspheres to spontaneously adjust their positions, finding an arrangement with minimum free energy to form a long-range ordered photonic crystal. The particles undergo a hydrothermal reaction under high temperature and pressure in an autoclave, causing dehydration condensation reactions in adjacent silanol groups. This significantly reduces the number of ionizable hydroxyl groups on the surface, resulting in a substantial decrease in negative charge density and double-layer thickness. The electrostatic repulsion is greatly weakened, and van der Waals forces become dominant. When the microspheres approach each other, they irreversibly and randomly adhere together due to strong van der Waals forces, forming amorphous aggregates. Coating the outermost layer with a thin SiO2 shell reconstructs a silanol-rich "active surface" on the original microsphere surface, restoring high surface charge and colloidal stability. This "surface chemical repair" strategy rebuilds the strong electrostatic repulsion necessary for assembly, effectively suppressing non-specific aggregation and thus significantly improving the long-range order and optical quality of the photonic crystal.

[0046] 4. The Principle of Fine Patterning Capability: Patterning capability depends on two aspects—manufacturability and pattern definition mechanism. Manufacturability: Mid-infrared carbon dioxide lasers are used for patterning, utilizing the photothermal interaction mechanism between the 10.6 μm wavelength laser and the material to achieve selective removal with micron-level precision. Since laser energy mainly diffuses to the surroundings through thermal conduction, and the long wavelength of the carbon dioxide laser results in a large focused spot size, by precisely controlling the laser power, scanning speed, and pulse duty cycle, the heat-affected zone can be controlled within the microsphere scale, achieving selective etching with clear pattern edges and resolution meeting micron-level requirements. The microspheres in the laser-irradiated area and the luminescent molecules encapsulated within them are completely removed, forming an etched area without luminescence capability; while the unirradiated area retains the intact structure of the microspheres and its long afterglow performance, thus achieving spatial complementarity between the luminescent and etched patterns. The unique feature of this invention is that the pattern is not only reflected in the presence or absence of microspheres (physical morphology), but also in the selective existence of the luminescent function in the region, which allows the pattern information to be read in two modes (observing the structural color pattern under natural light and observing the afterglow pattern after ultraviolet excitation), greatly improving the information capacity and the difficulty of anti-counterfeiting.

[0047] In summary, this invention enhances the structural color brightness through a high-refractive-index ZnS core, achieves stable long afterglow by encapsulating luminescent molecules in a double-layer SiO2 shell, and enables micron-level patterning through laser direct writing. The synergistic effect of these three elements successfully prepares a novel photonic crystal material that combines high-brightness angle-dependent structural color with patternable long afterglow luminescence, effectively solving the problems of dim structural color, unstable luminescence, and low patterning precision in existing technologies.

[0048] The beneficial effects of this invention are:

[0049] This invention provides a method for preparing and applying a high-refractive-index contrast patternable long-afterglow photonic crystal. Its core lies in the integration of a synergistic technical path—"core synthesis, inner shell coating, hydrothermal encapsulation, outer shell layer, self-assembly, and laser etching"—achieving breakthroughs simultaneously at three levels: material creation, process implementation, and device application. Specifically, this invention constructs high-refractive-index core-shell structured microspheres, combining controllable self-assembly and laser fine etching technology to achieve the integrated functionality of photonic bandgap, long-afterglow luminescence, and patterned microstructures. This results in a crystal with strong optical controllability, excellent afterglow performance, and flexible patterning characteristics, significantly enhancing its application potential in high-end anti-counterfeiting and optical information storage fields. The advantages are specifically reflected in the following five aspects:

[0050] 1. High refractive index contrast: The present invention uses ZnS with a high refractive index as the core to form a core-shell structure microsphere with a high effective refractive index, which forms a significant refractive index difference with air or medium, which is conducive to forming a high-quality photonic bandgap with strong optical effects.

[0051] 2. Excellent long afterglow performance: The long afterglow luminescent molecules are encapsulated in a SiO2 shell, which provides excellent protection to the SiO2 matrix, stabilizes the triplet excitons, reduces environmental quenching, and results in stable luminescence and a long lifetime. Simultaneously, the luminescence performance can be coupled with the photonic bandgap of the photonic crystal.

[0052] 3. Precise and flexible patterning capabilities: Utilizing laser etching technology, it is possible to process fine patterns at the micrometer scale, with a high degree of freedom in pattern design, making it suitable for the preparation of functional patterns with complex structures.

[0053] 4. Controllable preparation process: From nanoparticle synthesis to core-shell structure construction, and then to self-assembly and laser processing, each step has mature processes and strong controllability, which is conducive to batch preparation and performance regulation.

[0054] 5. Multifunctional Integration: The final product integrates the structural color of the photonic crystal, the photonic bandgap effect, long-persistent luminescence, and preset pattern information. The fabricated patterned photonic crystal film exhibits a bright structural color that gradually blue-shifts with increasing viewing angle under ordinary illumination, while also possessing tunable, high-brightness, and long-duration afterglow luminescence. This combination of angle-dependent structural color and long-persistent emission creates dual dynamic optical characteristics, giving the material unique advantages in visual recognition and optical information storage, significantly enhancing its practical value in high-end dynamic anti-counterfeiting, multi-level information encryption, and optical sensing. Attached Figure Description

[0055] Figure 1 Transmission electron microscopy images and diameter analysis of ZnS, ZnS@SiO2, and ZnS@CD-doped SiO2@SiO2;

[0056] a shows a transmission electron microscope image of ZnS nanoparticles and their diameter analysis;

[0057] b shows the transmission electron microscope image and diameter analysis of ZnS@SiO2 nanoparticles;

[0058] c represents a transmission electron microscope image and diameter analysis of ZnS@CD-doped SiO2@SiO2 microspheres;

[0059] Figure 2 High-resolution transmission microscopy images of ZnS@CD-doped SiO2@SiO2 microspheres clearly reveal the lattice structure of the doped carbon dots and ZnS cores in the composite microspheres;

[0060] Figure 3 Luminescence characterization of aqueous solution of ZnS@CD-doped SiO2 particles;

[0061] a represents the fluorescence and phosphorescence spectra (gating time: 2 ms; excitation wavelength: 351 nm);

[0062] b represents the afterglow lifetime decay curve;

[0063] Figure 4 Characterization of photonic crystals formed by ZnS@CD-doped SiO2@SiO2 impregnation and pulling;

[0064] a is a scanning electron microscope image of the formed photonic crystal;

[0065] b represents the angle-resolved reflection spectrum of the formed photonic crystal;

[0066] Figure 5 Photographs of the structural color and long-afterglow luminescence of patterned long-afterglow photonic crystals (from top to bottom, the core-shell structured microspheres have sizes of d...). ZnS = 145 nm, d shell = 58 nm, d ZnS = 145 nm, d shell = 85 nm, d ZnS = 145nm, d shell = 25 nm);

[0067] a is an angle-dependent structural color photograph of the pattern under sunlight;

[0068] b is a photo of the afterglow after the 365 nm ultraviolet excitation was turned off;

[0069] Figure 6 Luminescence characterization of aqueous solution of ZnS@4-PP-doped SiO2 particles;

[0070] a represents the fluorescence and phosphorescence spectra (gated time: 2 ms; excitation wavelength: 280 nm);

[0071] b represents the afterglow lifetime decay curve;

[0072] Figure 7 The average refractive index of ZnS@CD-doped SiO2@SiO2 composite microspheres with different ZnS core sizes and SiO2 shell thicknesses;

[0073] Figure 8 Normalized reflectance spectra of photonic crystals assembled from ZnS@CD-doped SiO2@SiO2 microspheres at 10° with different ZnS core sizes and SiO2 shell thicknesses;

[0074] a represents a ZnS core size of 145 nm, with different SiO2 shell thicknesses;

[0075] b represents ZnS core sizes of 100 nm and 170 nm, with different SiO2 shell thicknesses;

[0076] Figure 9 The afterglow intensity and lifetime of ZnS@CD-doped SiO2 microspheres at different reaction temperatures with a reaction time of 3 h;

[0077] Figure 10 The afterglow intensity and lifetime of ZnS@CD-doped SiO2 microspheres at a reaction temperature of 140℃ and different reaction times;

[0078] Figure 11 The microspheres are composed of ZnS (145 nm), SiO2 (274 nm) and ZnS@CD-doped SiO2@SiO2 microspheres (d ZnS = 145nm, d shell The relative reflection properties of the photonic crystal prepared at different incident angles (= 25 nm). Detailed Implementation

[0079] The embodiments of the present invention will be described in detail below with reference to specific examples. These examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions or conditions recommended by the manufacturer shall apply in the examples. Reagents or instruments used, unless otherwise specified, are all commercially available products.

[0080] The core of this invention lies in designing and synthesizing a composite microsphere with a "core@composite shell@outer shell" structure, and then using this microsphere to self-assemble into a photonic crystal, followed by selective patterning via laser etching. This method employs a wet chemical process to prepare monodisperse ZnS nanoparticles, then uses a modified Stöber method to grow a SiO2 shell on the surface of the ZnS particles, and encapsulates luminescent molecules within the SiO2 shell using a hydrothermal reaction. Subsequently, an undoped SiO2 layer is coated on the outermost layer, ultimately yielding a core-shell structured ZnS@luminescent molecule-doped SiO2@SiO2 composite microsphere. Using this as a building block, a three-dimensional photonic crystal with a specific pattern is fabricated using laser etching technology. The obtained photonic crystal exhibits long afterglow luminescence after ultraviolet light excitation ceases; under natural light conditions, its pattern displays a bright structural color that gradually blue-shifts with increasing viewing angle. The high refractive index of the ZnS core achieves a high refractive index contrast between the microsphere and the medium, thereby enhancing the brightness of the structural color. Precise patterning design enables micro-area optical control of photonic crystals, significantly enhancing their application potential in information storage and anti-counterfeiting technologies.

[0081] Example 1

[0082] A method for fabricating a high refractive index contrast patterned long afterglow photonic crystal:

[0083] Step 1: In a 250 mL flask, 4.0 g of polyvinylpyrrolidone was dissolved in 75 mL of deionized water and allowed to dissolve for 30 min at room temperature. The mixture was then sonicated for 10 min to form a homogeneous and transparent solution. The solution was then placed in an oil bath and heated to 75 °C at a rate of 800 r / min. After maintaining the temperature at 75 °C for 5 min, 1.5 g of thioacetamide was added. After 15 min, 200 μL of concentrated nitric acid was added, and stirring was continued for 15 min. Simultaneously, 2.97 g of zinc nitrate hexahydrate was dissolved in 5 mL of deionized water, and this solution was rapidly added to the reaction system with a stirring speed of 1000 r / min to form smaller particles. After 3 min, the stirring speed was reduced to 500 r / min, and the reaction was continued for 2 h, generating ZnS nanoparticles with an average particle size of 100 nm. When the reaction time was increased from 2 h to 3 h, the size of the ZnS particles increased from 100 nm to 120 nm. Subsequently, 0.6 g of zinc nitrate hexahydrate was dissolved in 1 mL of deionized water and added to the reaction system. After reacting for 1 h, ZnS particles with an average particle size of 145 nm were obtained. Similarly, 0.6 g of zinc nitrate hexahydrate was dissolved in 1 mL of deionized water and added to the reaction system to obtain ZnS particles with an average particle size of 170 nm. By adjusting the content of zinc nitrate hexahydrate and the reaction time, ZnS particles with different average particle sizes can be obtained. After the reaction was completed, the product was collected by centrifugation and washed. Finally, it was measured at 300 mg / mL.-1 The concentration is dispersed in anhydrous ethanol for further use.

[0084] Step 2: Mix 10 mL of ZnS (145 nm) ethanol dispersion, deionized water, and ammonia in a 50 mL flask at a volume ratio of 4:1:1 and stir at room temperature for 20 min. Then, add 0.4 mL of tetraethyl silicate and an equal volume of ammonia solution in a 3.8 μL / min solution. -1 The solution was added dropwise to the reaction system at a certain rate. After stirring for 6 h, ZnS@SiO2 particles with a SiO2 shell thickness of 20 nm were obtained. By changing the volume of tetraethyl silicate and ammonia solution added, SiO2 shells of different thicknesses could be obtained. After the reaction was completed, the product was collected by centrifugation and washed three times with anhydrous ethanol. The synthesized ZnS@SiO2 particles were then dispersed in 3.75 mL of deionized water for further use.

[0085] Step 3: Mix 8 mL of phosphoric acid, 4 mL of ethanolamine, and 16 mL of deionized water, and stir vigorously at 800 r / min, during which a strong exothermic reaction occurs. After cooling the mixture to room temperature, transfer it to a microwave oven and heat at medium power (700 W) for 8 min. After the reaction is complete, the resulting black solid is collected and diffused into 40 mL of deionized water using ultrasound. Subsequently, sodium carbonate is added in small amounts several times to neutralize the mixture until the pH reaches 7.0. The mixture is then centrifuged at 12000 r / min for 10 min to remove large carbon particles, and the supernatant is collected. The supernatant is further purified through a 0.23 μm membrane, and finally, 60 mg of carbon black is added to the solution to remove residual salts and precursors. The mixture is dried under low pressure, and the carbon dots are collected and diluted to 8 mg / mL. -1 For further use.

[0086] Step 4: Transfer 3.75 mL of ZnS@SiO2 dispersion to a 5 mL glass bottle, then add 0.25 mL of carbon dot dispersion and sonicate to mix thoroughly. Place the glass bottle in a PTFE-lined high-pressure reactor, adding an appropriate amount of deionized water until the water level is level with the surface of the mixed solution. Seal the reactor and place it in a forced-air drying oven at 140℃ for 3 h. After the reaction is complete, centrifuge to collect the ZnS@CD-doped SiO2 particles, wash them, and disperse them in 10 mL of anhydrous ethanol for further use.

[0087] Step 5: After the hydrothermal reaction is complete, the ZnS@CD-doped SiO2 ethanol dispersion, deionized water, and ammonia solution are mixed in a 4:1:1 volume ratio in a 50 mL flask and stirred at room temperature for 20 min. Then, 0.15 mL of tetraethyl silicate and an equal volume of ammonia solution are added in a 3.8 μL / min... -1 The solution was added dropwise to the reaction system at a rate of [missing information]. After stirring the reaction for 2 h, ZnS@CD-dopedSiO2@SiO2 particles were obtained, with the outermost SiO2 shell thickness being 5 nm.

[0088] Step 6: The glass slide was ultrasonically cleaned for 2 minutes to remove surface impurities, and then fixed onto the dip-coating apparatus. A beaker containing 4 mL of a 6 wt% ethanol dispersion of ZnS@CD-doped SiO2@SiO2 was placed directly below the dip-coating apparatus to promote the controlled formation of the photonic crystal. The optimized process parameters were: a dipping speed of 2 μm / s. -1 The descent rate is 300 μms -1 The soaking time was 120 seconds, the dwell time was 120 seconds, the lifting height was 16 mm, and the number of lifting times was 8.

[0089] Step 7: Perform laser scanning etching on the 3D photonic crystal obtained in Step 6. A commercially available mid-infrared carbon dioxide laser direct writing system is used for processing. The main parameters are set as follows: laser wavelength: 10.6 μm; average power: 6 W (this power has been optimized through pre-experiments to ensure effective removal of the photonic crystal microspheres); scanning speed: 20 mm / s; scanning spacing: 1200 ppi. Use the accompanying computer-aided design software to draw the vector diagram of the required pattern (such as a snowflake pattern), import it into the laser scanning system, modify the above parameters, focus, and then etch the photonic crystal film. After completion, a snowflake-shaped photonic crystal pattern will be obtained. The patterned area exhibits angle-dependent bright structural color under normal illumination. After external excitation is stopped, it further exhibits a long-afterglow luminescence snowflake shape, realizing the integration of dual optical information of static structural color and dynamic afterglow luminescence.

[0090] ZnS, ZnS@SiO2, and ZnS@CD-doped SiO2@SiO2 synthesized during Example 1 were imaged using a Hitachi HT 7800 transmission electron microscope with an accelerating voltage of 100 kV. Figure 1 As shown, the synthesized nanoparticles are uniform in size and well-dispersed, which is beneficial for the formation of three-dimensional photonic crystal thin films. Figure 1As shown in Figures (a), (b), and (c), these are transmission electron microscopy (TEM) images and particle size distribution histograms of ZnS, ZnS@SiO2, and ZnS@CD-doped SiO2@SiO2 particles, respectively. The figures show that all three types of nanoparticles have uniform particle size. Compared to the other two types, ZnS exhibits slightly poorer dispersibility. However, after being coated with a SiO2 shell, the nanoparticles demonstrate excellent dispersibility, which is beneficial for the subsequent fabrication of three-dimensional photonic crystals.

[0091] like Figure 2 As shown, HRTEM images of ZnS@CD-doped SiO2@SiO2 microspheres reveal small nanoparticles embedded in the SiO2 shell, with a crystal plane spacing of 0.20 nm, corresponding to the (100) crystal plane of a graphite-like structure; simultaneously, the spacing of the ZnS cores is 0.27 nm, consistent with the (200) crystal plane of cubic ZnS. These crystal plane spacings further confirm that the carbon dot particles are encapsulated and embedded in the SiO2 shell, and the SiO2 matrix stabilizes the triplet excitons, enabling the final photonic crystal to achieve long afterglow luminescence.

[0092] like Figure 3 As shown, under 351 nm UV excitation, ZnS@CD-doped SiO2 particles exhibit blue fluorescence at 426 nm. The gated spectrum with a delay time of 2 ms shows that they also emit green phosphorescence concentrated at 532 nm with an afterglow lifetime of 1.39 s.

[0093] like Figure 4 As shown, SEM images of the samples obtained by dip-coating ZnS@CD-doped SiO2@SiO2 microspheres confirm that the resulting films possess highly ordered three-dimensional structural features. This conclusion is further supported by the angle-dependent structural color phenomenon, a hallmark feature of photonic crystals. Specifically, as the incident angle increases from 10° to 60°, the reflected wavelength blue-shifts from 518 nm to 453 nm.

[0094] like Figure 5 As shown, the core-shell structure dimensions are d ZnS = 145 nm, d shell = 58 nm and d ZnS = 145 nm, d shell Patterned photonic crystals composed of microspheres with a diameter of 85 nm exhibit a bright structural color that gradually blue-shifts with increasing angle under sunlight. The structural color varies depending on the size of the microspheres at the same angle, a phenomenon also confirmed by the Bragg equation. After ultraviolet excitation is turned off, the snowflake-shaped patterned region exhibits a green afterglow emission lasting for 7 seconds.

[0095] Example 2

[0096] This embodiment demonstrates that, in addition to carbon dots, other luminescent molecules can be encapsulated within the SiO2 shell. As shown in step 4 of Example 1, 50 mg of ZnS@SiO2 particles and 6 mg of 4-phenylpyridine molecules (4-PP) were dispersed in 4 mL of deionized water and transferred to a 5 mL glass bottle, where they were ultrasonically dispersed and mixed thoroughly. The glass bottle was placed in a polytetrafluoroethylene-lined high-pressure reactor, and an appropriate amount of deionized water was added to the liner until the water level was flush with the surface of the mixed solution. The reactor was sealed and placed in a forced-air drying oven, where it was reacted at 180°C for 3 h. After the reaction, the ZnS@4-PP-dopedSiO2 particles were collected by centrifugation, washed, and dispersed in 10 mL of anhydrous ethanol for further use.

[0097] like Figure 6 As shown, under 280 nm UV excitation, ZnS@4-PP-doped SiO2 particles exhibit fluorescence at 350 nm. The gated spectrum with a delay time of 2 ms shows that they also emit cyan phosphorescence concentrated at 476 nm with an afterglow lifetime of 3.37 s.

[0098] Example 3

[0099] This embodiment demonstrates a scheme for precisely designing the bandgap of photonic crystals by adjusting the core-shell structure parameters to control the refractive index of microspheres. As shown in step 1 of Example 1, monodisperse ZnS particles with diameters of 100, 145, and 170 nm were synthesized. Following the method shown in step 2 of Example 1, by changing the amount of tetraethyl orthosilicate (TEOS) added, increasing the TEOS amount from 0.35 mL to 1.3 mL, the shell thickness could be increased from 15 nm to 80 nm. ZnS@CD-doped SiO2@SiO2 nanoparticles with different core and shell sizes were synthesized in subsequent steps of Example 1, maintaining the outermost pure SiO2 shell at 5 nm, and then impregnated and pulled to prepare a three-dimensional photonic crystal thin film. The final formula for calculating the refractive index of the composite microspheres is as follows:

[0100] (1)

[0101] in, and These represent the refractive indices of ZnS and SiO2, respectively. and These represent the diameters of the ZnS core and the final core-shell structured microspheres, respectively. For example... Figure 7As shown, by changing the sizes of the ZnS core and SiO2 shell, core-shell microspheres with refractive indices ranging from 1.49 to 1.69 can be obtained, and the refractive index increases with increasing core size. Subsequently, the bandgap modulation mechanism was investigated by characterizing the optical properties of photonic crystals assembled from microspheres with different refractive indices. The results are as follows... Figure 8 As shown, for a 145 nm ZnS core, increasing the total thickness of the CD-doped SiO2 and pure SiO2 layers from 20 nm to 85 nm redshifts its photonic bandgap at a 10° incident angle from 480 nm to 708 nm. Furthermore, coating a 100 nm ZnS core with a 50 nm thick SiO2 layer produces a photonic bandgap in the cyan spectral region, while a shell of the same thickness coating a 145 nm ZnS core results in a bandgap shifted to the yellow region. Similarly, compared to the green bandgap produced by coating a 145 nm ZnS core with a 40 nm shell, a shell of the same thickness coating a 170 nm ZnS core redshifts the bandgap to the orange-red spectral region. The above results demonstrate that by systematically designing the geometric parameters of core-shell microspheres, a wide range of continuous control over their effective refractive index can be achieved. Based on this, the photonic bandgap position of the final photonic crystal can be precisely and predictably located, thereby achieving active design and tailoring of the material's optical properties.

[0102] Example 4

[0103] This embodiment explores the effect of hydrothermal temperature on the reaction of the encapsulated carbon dots. Except for the hydrothermal temperature, the raw materials, proportions, and preparation steps are the same as in Example 1. The precursor solution was placed in a high-pressure reactor lined with tetrafluoroethylene and reacted for 3 h at 80℃, 100℃, 120℃, 140℃, 160℃, 180℃, and 200℃, respectively. Figure 9 Carbon doping into the SiO2 matrix can be achieved at reaction temperatures as low as 80°C, producing a green afterglow of 0.81 s. With increasing reaction temperature, both the afterglow lifetime and intensity show a trend of first increasing and then decreasing, reaching a peak of 1.39 s at 140°C and decreasing to 0.74 s at 200°C. This example demonstrates that carbon doping can be effectively achieved over a wide range from 80°C to 200°C by controlling the hydrothermal temperature, with 140°C being the optimal temperature for obtaining the best afterglow performance. This provides a key process parameter for precisely controlling the optical properties of the material.

[0104] Example 5

[0105] This embodiment investigates the effect of hydrothermal reaction time on the encapsulation of carbon dots. Keeping other conditions unchanged from Example 1, the hydrothermal reaction temperature was 140°C, and the variable was the hydrothermal reaction time. Experiments were conducted at the optimal reaction temperature of 140°C, with hydrothermal reaction times controlled at 0.5 h, 1 h, 2 h, 3 h, and 4 h, respectively. Figure 10 Extending the reaction time initially improves the intensity and lifetime of the afterglow, both reaching their peak values ​​at 3 hours, with a lifetime of 1.39 seconds and the afterglow intensity integral reaching its peak. Subsequently, further extending the reaction time leads to a decrease in afterglow performance, with the afterglow lifetime dropping to 0.98 seconds at a reaction time of 4 hours. This trend indicates that the reaction system has reached an optimal equilibrium state, where the doped carbon dots exhibit the highest degree of stability within the SiO2 matrix. This embodiment determined the optimal reaction time for preparing this long afterglow material at 140°C to be 3 hours, providing a key parameter for process control.

[0106] Example 6

[0107] This embodiment compares the reflectance properties of photonic crystals composed of high-refractive-index ZnS@CD-doped SiO2@SiO2 composite microspheres and single-component microspheres (ZnS, SiO2). Using ZnS (145 nm particle size), SiO2 (274 nm particle size), and ZnS@CD-doped SiO2@SiO2 composite microspheres (ZnS core diameter 145 nm, SiO2 shell thickness 25 nm) as building blocks, photonic crystal films of similar thickness were prepared according to the dip-coating self-assembly process of Example 1, and their relative reflectance spectra at an incident angle of 10° were measured. The results are as follows: Figure 11 As shown, at the test angle, the photonic crystal film based on ZnS@CD-doped SiO2@SiO2 composite microspheres exhibits an integrated reflection intensity approximately 6 times that of a ZnS film of the same thickness and approximately 2.2 times that of a SiO2 film. This data fully demonstrates that the ZnS@CD-doped SiO2@SiO2 composite microspheres prepared in this invention, due to their unique core-shell structure and high effective refractive index, can be assembled into photonic crystals with significantly enhanced optical performance, providing a key material basis for achieving high brightness and high contrast structural color output.

[0108] The embodiments described above in this application are merely for clearly illustrating the technical solutions and implementation processes of the present invention and should not be construed as limiting the scope of protection of the present invention. Any reasonable changes, equivalent substitutions, or adaptive improvements made under the core technical concept of the present invention regarding material structure (such as ZnS core size, SiO2 shell thickness, carbon doping concentration), preparation process (such as hydrothermal reaction temperature and time, self-assembly method parameters), or performance control (such as refractive index range, afterglow lifetime, photonic bandgap position) should be considered to fall within the scope of protection of the claims of the present invention, as long as they ultimately achieve or optimize the purpose of synergistic control of long afterglow luminescence and photonic bandgap of the present invention.

[0109] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the scope of the technology disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a patternable long afterglow photonic crystal with high refractive index contrast, characterized by comprising the following steps: 1) Preparation of ZnS@SiO2 particles 1. 1) Monodisperse ZnS nanoparticles with uniform morphology and a particle size of 100-170 nm were prepared by wet chemical method; 1. 2) The ZnS nanoparticles obtained in step 1.1) are uniformly coated with a SiO2 shell with a thickness of 15-80 nm using the improved Stöber method to obtain ZnS@SiO2 particles; 2) Preparation of ZnS@luminescent molecular doped SiO2 particles The luminescent molecule solution with long afterglow luminescence potential and the ZnS@SiO2 particle dispersion obtained in step 1) are uniformly dispersed in deionized water and placed in a high-pressure reactor for hydrothermal reaction to encapsulate the luminescent molecules in the SiO2 shell of the ZnS@SiO2 particles, thus obtaining ZnS@luminescent molecule-doped SiO2 particles. 3) Preparation of ZnS@luminescent molecular doped SiO2@SiO2 composite microspheres The ZnS@luminescent molecule-doped SiO2 particles obtained in step 2) are uniformly coated with a SiO2 shell layer with a thickness of 5-10 nm using the improved Stöber method to obtain ZnS@luminescent molecule-doped SiO2@SiO2 composite microspheres with a refractive index of 1.49-1.

69. 4) Preparation of three-dimensional long afterglow photonic crystals The ZnS@luminescent molecule-doped SiO2@SiO2 composite microspheres obtained in step 3) were prepared into a three-dimensional long afterglow photonic crystal using the vertical dip-coating method.

2. The preparation method according to claim 1, characterized in that, Step 1) Specifically:

1. 1) Polyvinylpyrrolidone was dissolved in deionized water and sonicated to obtain a homogeneous and transparent solution. The solution was heated to 70-80℃ and kept stable before adding thioacetamide. After 10-15 min, concentrated nitric acid was added and stirred for another 10-15 min to completely hydrolyze the thioacetamide, resulting in a clear and transparent reaction system solution. At the same time, zinc nitrate hexahydrate was dissolved in deionized water and the solution was rapidly added to the reaction system with a stirring speed of 1000 r / min to form small particles. After 3 min, the stirring speed was reduced to 500 r / min, and the reaction was continued for 2-5 h. After the reaction was completed, the particles were washed with deionized water to obtain monodisperse ZnS nanoparticles with uniform morphology and a particle size of 100-170 nm. 1.2) Disperse the ZnS nanoparticles obtained in step 1.1) in ethanol, then mix them with deionized water and ammonia at a volume ratio of 4:1:1 at room temperature until homogeneous. Then, add tetraethyl silicate and an equal volume of ammonia solution at a rate of 3.8 μL / min. -1 The solution is added dropwise and stirred to produce ZnS@SiO2 particles.

3. The preparation method according to claim 1 or 2, characterized in that: In step 2), the luminescent molecule with long afterglow luminescence potential is a nitrogen-doped carbon dot, 4-phenylpyridine, or 4,4'-bipyridine; The temperature of the hydrothermal reaction is The reaction time is .

4. The preparation method according to claim 3, characterized in that, Step 3) specifically involves: First, disperse the ZnS@luminescent SiO2 particles obtained in step 2) in ethanol, then mix them with deionized water and ammonia at a volume ratio of 4:1:1 at room temperature. Next, add tetraethyl silicate and an equal volume of ammonia solution at a rate of 3.8 μL / min. -1 The solution was dripped into the solution at a certain rate, and the reaction was stirred to obtain ZnS@luminescent molecular doped SiO2@SiO2 composite microspheres.

5. The preparation method according to claim 4, characterized in that, Step 4) specifically involves: The ZnS@luminescent molecularly doped SiO2@SiO2 composite microspheres obtained in step 3) were dispersed in anhydrous ethanol with a mass fraction of 6-10 wt% to form a dispersion. A clean substrate was vertically immersed into the dispersion using a vertical dip-pick method at a speed of 2 μms. -1 The speed is such that the dip-coating is performed on the substrate 4-8 times to obtain a three-dimensional long afterglow photonic crystal.

6. The preparation method according to claim 5, characterized in that: In step 4), the substrate is a glass substrate.

7. A high refractive index contrast patternable long afterglow photonic crystal, characterized in that: It is prepared by any one of the preparation methods described in claims 1-6.

8. The application of the high refractive index contrast patternable long afterglow photonic crystal of claim 7 in the preparation of optical anti-counterfeiting marks or dynamic information storage media.

9. A method for preparing an optical anti-counterfeiting label or dynamic information storage medium, characterized in that: As required, a preset pattern is fabricated on the high refractive index contrast patternable long afterglow photonic crystal as described in claim 7 using laser etching technology.

10. An optical anti-counterfeiting label or dynamic information storage medium, characterized in that: It was prepared by the method described in claim 9.